Load-velocity relationship variables to assess the maximal neuromuscular capacities during the back-squat exercise - Pérez-Castilla, A.; Jukic, I.; Janicijevic, D.; Akyildiz, Z.; Senturk, D.; Garcia-ra; García-Ramos, A. (Sports Health: A Multidisciplinary Approach, 2022)
Background: The relationship between the external load lifted and movement velocity can be modeled by a simple linear regression, and the variables derived from the load-velocity (L-V) relationship were recently used to estimate the maximal neuromuscular capacities during 2 variants of the back-squat exercise.